Relationship between glycaemic control with microalbuminuria and trace metals in patients with type 2 diabetes mellitus: A cross-sectional study from University of Ilorin teaching hospital, Nigeria - Abdul Azeez IM; Aliyu G G; Okesina A B; Oladosu O W Bello M B; Abdullahi M; Ajala A O (Journal of Krishna Institute of Medical Sciences University)
Background: Low serum levels of some trace metals have been associated with the severity of diabetes mellitus. An increase in Urinary Albumin Excretion (UAE) has also been identified as one of the risk factors that contribute to morbidity and mortality among patients with Type 2 Diabetes Mellitus (T2DM). Aim and Objective: This study aims to determine the relationship between serum trace metals (Mg, Zn, Mn, and Cr), UAE, and glycaemic control among patients with Type 2 Diabetes Mellitus (T2DM). Materials and Methods: This cross-sectional analytical study was carried out over three months. There were 304 participants, comprising 152 patients with T2DM and 152 age and sex-matched controls without Type 2 Diabetes mellitus. The Fasting Plasma Glucose (FPG), Glycated Albumin (GA), Glycated Serum Albumin (GSA), Glycated haemoglobin (HbA1c), UAE, and trace metals (Mg, Zn, Mn, and Cr) were analyzed. The data analysis in this study was done using SPSS Inc., Chicago, IL, USA. Parameters with p < 0.05 were statistically significant. Results: This study found reduced serum Mg and Zn in patients with T2DM. There was a positive correlation between markers of glycaemic control and UAE. Negative correlation exists between markers of glycaemic control and serum Mg and Zn. Also, the study demonstrated a negative correlation between UAE and serum Mg and Zn. Conclusion: This study demonstrated that the poorer the glycaemic control, the higher the urinary albumin level. The poor glycaemic levels were also adversely correlated with Mg and Zn serum levels.